2012
DOI: 10.1021/cg300325p
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Polymer Properties Important for Crystal Growth Inhibition—Impact of Chemically Diverse Polymers on Solution Crystal Growth of Ritonavir

Abstract: The use of supersaturating dosage forms, such amorphous dispersions, is an increasingly common approach for improving delivery of poorly water-soluble drugs. Crystallization must be prevented to maintain supersaturation, and so, the presence of an effective crystal growth inhibitor in solution is desirable to prolong supersaturation. In this study, the effectiveness of a group of chemically diverse polymers, including a number of novel cellulose derivatives, at inhibiting the crystal growth of ritonavir from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
193
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 191 publications
(207 citation statements)
references
References 42 publications
11
193
2
1
Order By: Relevance
“…However, unstable supersaturated drug precipitates from the solution in order to reach equilibrium state [46]. During drug precipitation, adsorption of polymer on the particles surface can prevent crystal growth by blocking active surfaces and providing steric stabilization [47]. Moreover, hydrogen bonding between the drugs and polymers may help to the maintenance of supersaturation state [48].…”
Section: In Vitro Dissolution Testingmentioning
confidence: 99%
“…However, unstable supersaturated drug precipitates from the solution in order to reach equilibrium state [46]. During drug precipitation, adsorption of polymer on the particles surface can prevent crystal growth by blocking active surfaces and providing steric stabilization [47]. Moreover, hydrogen bonding between the drugs and polymers may help to the maintenance of supersaturation state [48].…”
Section: In Vitro Dissolution Testingmentioning
confidence: 99%
“…Additives such as polymers at low solution concentrations do not generally enhance equilibrium crystalline solubility of small molecules (28). Rather, they inhibit nucleation (5,(29)(30)(31)(32), and/or crystal growth (33)(34)(35)(36) and thereby stabilize supersaturated solutions (29). In contrast, the other additives such as surfactants or complexing agents typically increase equilibrium solubility.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies were conducted by Alonzo et al (2012) and Oucherif et al (2013) who analysed and modelled the growth and nucleation kinetics of felopidine in the presence of HPMC [33], [34]. The same research group also used HPMC to nucleate amorphous flutamide [14] and several other polymeric additives to inhibit growth of ritonavir [35][36][37]. In some cases polymers can promote growth: in particular, it was found that a very small amount of ethylene dinitrotetraacetic acid disodium salt (EDTA) could accelerate the growth of potassium dihydrogen phosphate (KDP) crystals by forming molecular complexes with adventitious impurities in solution and eliminating their inhibiting effect [38].…”
Section: Introductionmentioning
confidence: 68%